(untitled) (Prostor, 2023)
European Commission has obliged Horizon 2020 and Horizon Europe beneficiaries to specify the dissemination and exploitation of their funded activities’ outcomes. In this way, research results can be extended to benefit the wider society. However, beneficiaries have difficulties meeting these goals due to the overlap between dissemination and exploitation and the uncertainty of how to translate research activities and outputs into socio-economic benefits for the society. This paper developed a framework based on the business model canvas to operationalise an approach to exploitation. The framework was tested within the EU-funded research project C3Places in the fields of urban planning and sustainable spatial development. The resulting reference framework can be used as a guideline for the design and development of research project exploitation plans. It is especially valuable for projects in the fields which usually do not have ‘sellable’ or even marketable outcomes and products but rather result in soft measures and recommendations for public policies. Accordingly, it can support the decision-making processes of both policymakers and private organisations.